Governing the Commons? : Water and Power in Pakistan's Indus Basin - Jacoby, Hanan G.; Mansuri, Ghazala (World Bank, Washington, DC, 2018)
Surface irrigation is a common pool resource characterized by asymmetric appropriation opportunities across upstream and downstream water users. Large canal systems are also predominantly managed by the state. This paper studies water allocation under an irrigation bureaucracy subject to corruption and rent-seeking. Data on the landholdings and political influence of nearly a quarter million irrigators in Pakistan's vast Indus Basin watershed allow the construction of a novel index of lobbying power. Consistent with a model of misgovernance, the decline in water availability and land values from channel head to tail is accentuated along canals having greater lobbying power at the head than at the tail.